Exploring self expression and femininity in food photography: the artworks of the women photographer community "Kompakers Jogja" - Wibowo, Arif Ardy; Abrar, Ana Nadhya; Yuwono, Ardian Indro (Gelar: Jurnal Seni Budaya, 2024)
This study aims to analyze of the expressions of femininity in food photography as carried out by Kompakers Jogja. Photography has historically been established inside male-dominated domains. Unlike the historical context where photography has consistently been associated with male-dominated, Kompakers Jogja presents a contrasting perspective that questions the established norms of male dominance. This research explore the diverse viewpoints of ten individuals using a combination of photovoice and photo-elicitation. Through the application of qualitative content analysis within the thematic framework of femininity in photography, categorized as Theatricality, Tactility, Softness, and Hybridity. The analysis reveals that community members infuse distinct feminine sensibilities in their photography, as corroborated through visual scrutiny and validated during photo-elicitation. Prevalent among these manifestations are theatricality and hybridity, exemplified by strategic prop placement and digital enhancements aimed at augmenting the aesthetic allure of the captured images. In addition, tactility becomes important, especially when carefully choosing angles to elicit gustatory wants. Although the works of the members exhibit some softness, they serve more as supporting element. In summary, the Kompakers Jogja depict motifs that subtly and intricately symbolize femininity in their photography. This research shows the distinct characteristics linked to the facets of femininity as expressions of women's self-identity.